Sumatra Fairytale Theme Park - Merry Deria K Lase; Pedia Aldy; Ratna Amanati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
People need entertainment, one of them is have recreation to recreation park. Recreation park in Pekanbaru city is very minimal and limited. The lack of recreational park in Pekanbaru is the reason to built a Theme Park. Sumatra Fairytale Theme Park takes on fairytale as a theme of the park. Tale is one of Indonesia's cultural heritage is passed down through each generation. Fairy tales are drawn from five provinces, namely: Aceh, North Sumatra, Riau, Jambi and West Sumatra. The design pattern and space in order to be considered because the activity is in the room or indoor. The completion of the architectural design theme Postmodern architecture of choice for solving existing problems. The principles of postmodern architecture by Charles Jencks, namely: double coding, hybrid, and the metaphor became the foundation for creating Sumatra Fairytale Theme Park. In this design concept used pleasure and fantasy concepts (fun and fantasy). This concept is applied to the fabric, the pattern space, and circulation are designed as attractive as possible to provide a different experience and atmosphere so as to create a fantasy or imagination for tourists who come.Keywords : Theme Park, Indoor, Fairy Tales, Postmodern Architecture